PEMODELAN EVALUASI KINERJA SUPPLIER DENGAN METODE ANALYTIC HIERARCHY PROCESS (AHP) PADA LAYANAN OBAT RUMAH SAKIT - Yuliawati, Dona; Sanusi, Anuar (244-5567)
Efforts to achieve improved quality of service and increase the degree of optimal health for the community, organized through maintenance approach, health promotion (promotion), disease prevention (preventive), healing (curative), and the restoration of health (rehabilitation), which implemented a comprehensive, integrated , and sustainable. One of the efforts in the field of health care is to improve the quality of service through increased accuracy, rationalization and efficiency of the use of drugs, preparation of a list of essential drugs which put emphasis on cost optimization with these medicines are absolutely essential. List of Essential Medicines, which is a general list of standard drugs that have been published and are set by the Minister of Health.Â The evaluation process requires a method that can facilitate the assessment and decision making, as in decision making related to the criteria and the number of alternative suppliers, it is necessary to use a valuation technique that is effective and not too complex, but gives accurate results. This evaluation also involves an assessment of the hospital management or parties related to the supplier so that the accuracy of ratings given by each respondent is essential.AHP is a method to rank alternative decision in choosing one of the best when decision makers and have a wide criteria. In AHP-making hierarchy is used to decompose the problem into the smallest section. The hierarchy consists of several levels, namely objectives, criteria, sub-criteria and altervative.Keywords : Quality of Service Hospital, Supplier Evaluation, Analytic Hierarchy Â Process (AHP)